Processing Fishery Products for Community Food Security at the East Kutai Regency - Suprianto Suprianto; Eny Heriyati; Anshar Haryasakti; Imanuddin Imanuddin; Rosdianto Rosdianto (Universitas Muhammadiyah Palembang, 2023)
In order to increase the utilization of fisheries potential, it is necessary to diversify fish processing. East Kutai is a district that has the potential to produce fisheries, especially from fishing. The catch of sea fish and freshwater fish in East Kutai Regency in 2020 was 5,294 tons. Diversifying fish processing is one means of increasing community food security. The STIPER East Kutai Marine Science Study Program plays a role in helping the government to increase food security through exhibition activities at the